A STUDY ON THE THERMAL COMFORT OF TRADITIONAL MALAY HOUSES IN SAMBAS CITY - ZAIN, ZAIRIN; Nadiya, Nadiya (Border: Jurnal Arsitektur, 2025)
External threats such as animals, climate change, and weather conditions are commonly known factors that determine the house's primary function, which is to provide shelter and protection. The structural characteristics of the architecture of the traditional Malay House are unique in their distinctive construction techniques, design elements, functions, and decorative features. These houses, passed down through generations, have historically served as essential spaces for communal living. Thermal comfort in buildings refers to physical and physiological satisfaction, often assessed using empirical equations. This study evaluates the thermal comfort levels of traditional Malay houses in Sambas City. A descriptive quantitative approach is employed, utilizing Computational Fluid Dynamics (CFD) simulations conducted through Autodesk Inventor software to analyze indoor airflow patterns. Additionally, on-site measurements investigation is employed using an anemometer to assess wind speed, a hygrometer to determine humidity levels, and a thermometer to measure air temperature. The findings indicate that none of the case study houses meet the thermal comfort standards established by KEMENKES (Indonesian Ministry of Health) and SNI (Indonesian National Standard). As a result, residents often experience discomfort and resort to artificial ventilation at specific times to improve indoor conditions.